Exploring the impact of parental communication on the academic achievement of children studying in non-formal primary schools in Bangladesh - Md. Aktaruzzaman Khan; Yakin Afrin; Muhammad Lutful Hasan (Britain International for Academic Research (BIAR) Publisher, 2026)
This study aims to identify the influence of parental communication on their children's academic achievement in non-formal primary schools in Bangladesh. Numerous studies have investigated the relationship between parents' active participation and their children's academic achievement in formal education settings. There is limited research on how parental communication influences their children’s academic performance studying in non-formal schools, focusing on schools in underserved areas. Using a qualitative approach, data were collected from 20 students, 20 parents, and two grade four teachers from two non-formal schools in two districts of Bangladesh, Dhaka and Chattogram. Semi-structured interview questionnaires are used to collect in-depth data from the participants. However, a small amount of quantitative data has also been collected and analyzed to meet the requirements of the study. Thematic data was used to analyze and present the data. The study found a positive correlation between parental communication and their children's academic achievement. Notably, the study found that even parents with low income and less educational degrees who maintain regular communication with school and teachers significantly enhance their children's motivation and academic activities. The research also uncovers barriers such as parental time constraints and a lack of awareness about educational support strategies. Furthermore, the study recommends policy interventions and community-based initiatives to increase and emphasize parental communication in improving academic achievement in underserved communities. By understanding the role of parental communication in promoting children's academic success in non-formal settings, the study can provide insights into the design and implementation of effective educational programs and policies for this population.